Обґрунтування параметрів процесу оброблення рідких та молочних продуктів імпульсними електричними полями - Святненко, Роман Сергійович (My University, 2021)
Дисертація присвячена вирішенню актуальної проблеми молочної галузі використання енергії імпульсних електричних полів для подовження терміну зберігання молочних продуктів з обґрунтуванням параметрів процесу. На основі математичного моделювання процесів обробки молока імпульсними електричними полями була розроблена модель процесу виділення енергії в робочій камері, встановлено механізм процесів інактивації мікроорганізмів в молоці в камерах проточного типу. Встановлено відсутність негативних наслідків на фізико–хімічні показники молока після оброблення ІЕП. Запропоновано енергоощадну технологію оброблення рідких молочних продуктів з використанням енергії імпульсних магнітних полів, яка у поєднанні з тепловим обладнанням для рекуперації тепла забезпечує високоефективне оброблення молока шляхом зменшення тривалості його перебування в зоні критичних температур. Результати досліджень впроваджені у виробництво на підприємстві молочної галузі, та у навчальний процес Національного університету харчових технологій. The dissertation is devoted to the solving an actual problem of dairy branch of use of energy of pulsed electric fields for prolongation of expiration date of liquid dairy products with the substantiation of process parameters, for introduction of resource and energy saving technologies of intensification of industrial processes of food and biological value improvement. It was established that pulsed electric field treatment is the most energy efficient method for intensification of mass transfer processes and extension of the expiration date based on the analysis of the main electrophysical methods of liquid products processing. It was proved that the processing of milk by PEF in a closed chamber during 10 s heats it by 56oC, with the energy released in the chamber 56 kJ and the average energy consumption – 3.8 kW. It was experimentally established that the processing of whole milk by pulsed electric fields in the range of intensity 15… 30 kV/cm and duration 10 ... 30 s led to an increase in its temperature in the range of 45 ... 85°C due to redistribution of energy of pulsed electric fields into thermal energy. The increase in temperature correlates with the intensity and duration of processing. A mathematical model was developed for modeling the processes of inactivation of microorganisms in milk. It was established that the processing of milk by PEF at a voltage of 15 kV/cm led to irreversible inactivation of microorganisms at a processing time – 7 s, at a voltage of 20 kV/cm – 5 s, at a voltage of 25 kV/cm – 3 s, a voltage of 30 kV/cm – 2 s. A mathematical description of the processes of action of pulsed electric fields in a flow-type chamber with maximum energy efficiency was developed. The value of rational specific energy consumption in the flow mode during processing was set, which is Esp = 5.83 kW·h/m3, which is almost 4 times less than energy consumption during thermal pasteurization. The obtained result indicates that almost all the electromagnetic energy which reached the working chamber is released in it in the form of thermal energy. This is a fundamentally important factor, because both the electromagnetic components (electric and magnetic field strength, voltage and current in the working chamber) and thermal energy are synergistically directed factors. This unidirectional action leads to an increase in the degree of inactivation of microorganisms in processed liquid products. If the thermal energy released in the chamber is transferred by the heat exchanger to the untreated product that has not yet passed through the working chamber, the efficiency of energy ηe for this process is ηe≈85… 99.5%. The absence of a negative effect of PEF on the physicochemical and microbiological parameters of milk, within the rational parameters of the processing, was experimentally proved. The parameters of electropulse processing were determined to ensure processing of whole milk, whey and water with rational parameters. An analytical description of the change in physicochemical parameters of whole milk before and after processing by PEF for different processing parameters was made, which was confirmed by the obtained experimental data. Taking into account the results of scientific research, a new hardwaretechnological scheme of processing of liquid dairy products by PEF using pulsed magnetic field energy was developed, which in combination with thermal equipment for heat recovery provides highly efficient processing by reducing milk residence time at critical temperatures. The results of scientific research were introduced into production at the dairy plant LLC "Terebovlya Dairy Plant", technological requirements (TU U 10.8-02070938-228: 2017 "Milk-containing products obtained using electromagnetic processing") were developed, they were also introduced to the educational process of the National University of Food Technologies when teaching professional disciplines as well as in the implementation of course projects and diploma projects.
Keywords: процеси оброблення молока; пастеризація молока; імпульсні електричні поля; інактивація мікроорганізмів; milk processing; milk pasteurization; pulsed electric fields; inactivation of microorganisms